ANALISIS STRUKTUR WACANA DALAM ACARA âBAANTARAN JUJURANâ DI BANJARMASIN - Arifin, Johan (Vidya Karya Jurnal Kependidikan, 2015)
This research deals with the analysis of discourse structure in the show "Baantaran honesty" in Banjarmasin and the researcher concludes that this discourse structure consists of greetings, praise to God and the Prophet, respect for the arrival of the family of the bridegroom, Introduction words (in the language of Banjar-called " maantar pamandiran "), Core (delivery or receiving conduction), Acknowledgements and apology, Prayer, Closing (greeting). This type of approach used in this study is qualitative descriptive. The research is qualitative descriptive and aims of providing an overview of the case carefully. In the analysis of discourse structure, "baantaran jujuran" The discourse of dilivery of the bridegroom of the first and the discourse of acceptance of the bride is the response symbolized by R.